(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The main methods of teaching the Russian language traditionally include such as the word of the teacher, conversation, the method of observation over the language and speech material, the use of visualization, work with the book. The method of conversation is of great importance for the formation of students’ skills of consistent and deep thinking in connection with the assimilation of knowledge and skills in language.